Analysis of the Contextual Meaning of Confucian Moral Values of "Ren" and "Yi" in Hikayat Tiga Negara: (Analisis Makna Konteks Nilai Moral Konfusianisme Ren dan Yi dalam Karya Terjemahan Hikayat Tiga Negara) (Jurnal Bahasa, 2020)
This paper aims at investigating the contextual meaning of the Confucian moral values of "仁" (ren) and "义" (yi) in the situational contexts of Hikayat Tiga Negara. The situational context in a literary text is the episode that describes an event. This story centres on the themes of the values "仁" (ren) and "义" (yi), together with the descriptions of these values through the practices, beliefs and behaviour of characters in the situational contexts. Previous studies have shown that the interpretation of the contextual meaning of Confucian moral values is based on the sentential contexts to convey the general contextual meaning. The other problem is the subjective interpretation of the contextual meaning of the values, based on the motives and cultural contexts of the translators. In order to fill the gap in the studies on the interpretation of the meaning of values, which is confined to sentential contexts and subjective interpretation, this study focuses on the interpretation of the contextual meaning of the values based on their original meaning in the situational contexts. The research employs the method of synchronic system-based contextual meaning analysis to interpret the synchronic contextual meaning of "仁" (ren) and "义" (yi). By classifying the situational contexts into general context, distinctive context and extralinguistic context, the particular contextual meaning can be identified. The findings reveal that the contextual meanings of  "仁" (ren) are divided into general meaning, specific meaning and extralinguistic meaning, while the contextual meanings of  "义" (yi) are divided into general meaning, specific meaning, thematic meaning and interpersonal relationship-based meaning upon the classification of situational contexts. Besides this, the interaction between the intralinguistic and extralinguistic situational contexts also affects the interpretation of the contextual meaning of the values. This study presents the importance of discourse context to meaning in recreating Confucian moral values in the situational contexts of Hikayat Tiga Negara.Keywords: Confucian moral values, situational context, contextual meaning, interpretation, synchronic